Deception in simulation‐based education: a randomised controlled trial of the effect of deliberate deception on the performance of anaesthesia trainees. (3rd March 2022) - Friedman, Z.; Bould, M. D.; Pattni, N.; Malavade, A.; Nakatani, R.; Bansal, S.; Alam, F.
Summary: The use of deliberate deception in simulation allows for a level of realism that is not normally feasible. However, the use of deception is controversial, and carries the risk of psychological harm to learners. There are currently no quantitative data on the effect of deception on learner performance, making it difficult to judge its usefulness. The objective of this study was to examine the impact of deception on learners' performance during a life‐threatening scenario. In this simulation study, second‐year anaesthesia residents were randomly allocated into two groups: the non‐deception group was told that the participating consultant was acting a part, while the deception group was told that the consultant was a subject in the study. Learners then participated in a simulated crisis that presented them with situational opportunities to challenge the consultant regarding clearly wrong decisions. Two independent raters scored the performances using the modified advocacy‐inquiry scale. Forty‐four participants were analysed. The median (IQR [range]) highest scoring modified advocacy‐inquiry scale was 5.0 (4.5–5.1 [4.0–5.5]) for the non‐deception group and 4.0 (3.0–4.0 [2.5–5.0]) for the deception group, (p < 0.001), and the median total number of challenges per participant was 26.8 (21.0–31.1 [16.5–35.5]) and 18.0 (14.3–23.3 [7.0–33.0]), respectively (p = 0.001). Trainees exposed to deliberate deception, who thought that the consultant anaesthetist was a subject, had a less‐effective best challenge, likely mimicking real‐life behaviour. Deliberate deception appears to modify behaviour, particularly relating to communication involving hierarchical relationships. This technique may improve authenticity, especially with a steep power gradient, and so has demonstrable value which must be balanced against the ethical considerations.